RELATIONSHIP BETWEEN COMMUNICATION FACTORS AND ACADEMIC ACHIEVEMENT OF DEAF AND HARD OF HEARING STUDENTS IN SAUDI UNIVERSITIES - Manal Alkharji; Loh Sau Cheong, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The purpose of this study is threefold: 1) to validate the psychometric properties of communication factors’ measure, 2) to examine the degree of relationship between communication factors and the academic achievement of deaf and hard of hearing students (DHH) in Saudi universities, and 3) to test the moderating of gender in the relationship between communication factors and the students’ achievement. Data were collected from 298 DHH students using a quantitative survey. The study employed co-variance-based SEM using AMOS version 24. To test the psychometric properties for the communication factors, Confirmatory Factor Analysis (CFA) was employed. Second, a full-fledged SEM was conducted to test the relationship between the communication factors and the students’ academic achievement. Finally, to examine the moderating role of gender, a multi-group analysis was applied. The results indicated that the multidimensional hypothesized model of communication factors was empirically valid and reliable. The results also revealed a statistically significant relationship between communication factors and the students’ academic achievement, β = 0.23. Besides, the moderating role of students’ gender in the relationship between communication factors and the students’ academic achievement was also significant. In this regard, the change in the Chi-square was 48.06 while the change in CFIs and the value of the RMSEA were checked against the .001 and .05 cut-off scores respectively. Accordingly, the findings will contribute to increasing knowledge regarding communication factors in higher education programs for DHH students in the Kingdom of Saudi Arabia (KSA). The findings will also be useful to educators and policymakers in the Ministry of Education (MOE) in the field of deafness and hard of hearing. This research also has the potential to positively reflect on the performance of Saudi higher education institutions, thus enhancing DHH students' academic achievement.